Health promotion and health education: Theory and practice - Berić Bojana; Dželetović Anđelka (Vojnosanitetski Pregled)
Background. Since health promotion and health education are developing concepts around the world, the purpose of this paper was to compare theory and practice, at certain point in time in various countries. Methods. Data were collected using the structured direct interview. We approached 16 participants at the XVI World Conference on Health Promotion and Education. The responses of 11 participants were analyzed. Results. Health promotion is a separate profession in 4 out of 11 countries. Physicians are responsible for health promotion and education in all 11 countries. School was identified as a health promotion setting in all 11 countries, while community and hospital in 10. The Ottawa Charter (1986) guided the definition of health promotion for all participants, while 7 participants defined health promotion and health education differently. Conclusion. Unified definition of terms may allow similar practice at the international level; comprehensive approach to health includes all aspects of health, determinants, settings and practitioners; there occurs the need for health education as a separate profession globally.